World Bank Climate Knowledge Portal: Climate Analysis Tool. Powered by Climate Wizard - International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The World Bank Climate Knowledge Portal is powered by Climate Wizard. Climate Wizard enables technical and non-technical audiences alike to access leading climate change information and visualize the impacts anywhere on Earth. With Climate Wizard users can: view historic temperature and rainfall maps, view state-of-the-art future predictions of temperature and rainfall, and view and download climate change maps in a few easy steps. This site provides metrics on interpreting risks within specific sector or service, such as: • Water supply focused on total precipitation and two measures of dryness and drought conditions. • Flood risk driven by rainfall average, measures of wet day rainfall, and short term maximum rainfall intensities. • Human health focuses on temperature stress (hot and cold) to people: hottest and coldest single day temperature. • Energy demand incorporates heating and cooling demand using heating and cooling degree days. • Agro-ecosystem impacts to climate change incorporates many aspects including total precipitation, dry conditions, extreme hot and cold temperatures, and growing degree days.